Efeito de recurso floral na composição qualitativa de apitoxina - Lomele, Renata Leonardo [UNESP] (2014)
The migratory and highly defensive behavior of the africanized honeybees and their close contact with human populations can result in accidents, where treatment is often inefficient, emphasizing the need for the development of an effective honeybee antivenom. For this, the factors that may cause possible qualitative changes in apitoxin need to be evaluated, such as the food source of bees. In this study we verify differences in the mean number and intensity of the studied peaks generated by the HPLC/RF analysis of apitoxin, from hives kept in different floral sources. The feed from the flowering of Citrus sp., generated peaks corresponding to apamin, phospholipase, melittin and phospholipase isoform with higher intensity and higher total amount of peaks, but two samples not presented melittin isoform, a fact that can be associated to the genetic hive. Differently, the bees maintained in the area of Eucalyptus sp. showed the apitoxin with lower intensities for the peaks corresponding to these compounds, and also lower the total amount of peaks. The apitoxin of bees maintained in wild vegetation associated with artificial feeding had the highest peak intensity corresponding to melittin isoform and that originates from wild vegetation showed no dominant peaks. This variations suggest the diet influence in the composition of apitoxin, however the researches need to be deepened considering different floral resources available in other regions. This information can contribute to the future development of a representative, specific and safe antivenom for the treatment of bee’s stings.